PENENTUAN TERAS PANTAI PURBA BERDASARKAN POLA PENYEBARAN BIJIH TIMAH DI PULAU BANGKA - Herry Sulistiyo; Heru Sigit Purwanto (Jurnal Ilmiah MTG, 2009)
Exploration and exploitation of tin has been conducted in Bangka Island for over a century. Meanwhile the exploration technology of tin ore has remained stagnant. In the last 10 years there has not been any significant new finding in the filed of tin placer exploration technology. Implementation of “valley hunting” concept is no longer relevant in finding new resources inland as well as offshore. This is evident by the decreasing success ratio results in drilling explorations conducted.Tin ore is categorized as heavy mineral and is economically known as Cassiterite (SnO2) having a density between 6.7-7.1 and hardness of 7 on the Mohs scale. With its high resistance to abrasion and other physical properties, this mineral is often used as characteristic of a depositional phase of an area.The above characteristics have encouraged the writer to study the deposition pattern of tin ore by utilizing bore exploration results and attempt to establish a correlation using the Sea Level Changes theory in an effort to better understand how changes in sea level has influenced the deposition pattern of tin ore. By establishing a relation between changes in sea level and deposition of tin ore, the writer hopes to trace the historical shorelines that may provide indication of a secondary deposition of tin ore.